2013
DOI: 10.1007/s11255-012-0366-y
|View full text |Cite
|
Sign up to set email alerts
|

High-density lipoprotein in uremic patients: metabolism, impairment, and therapy

Abstract: Several studies have shown that HDL has altered antioxidant and anti-inflammatory effects in chronic uremia, either by the reduction in its antioxidant enzymes or by the impairment of their activity. Systemic oxidative stress, which is highly prevalent in chronic kidney disease (CKD) patients, has been shown to decrease antioxidant and anti-inflammatory effects of HDL and even transform it into a pro-oxidant and pro-inflammatory agent. For this reason, we believe that the propensity for accelerated cardiovascu… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
8
0

Year Published

2014
2014
2020
2020

Publication Types

Select...
6
1

Relationship

1
6

Authors

Journals

citations
Cited by 9 publications
(8 citation statements)
references
References 94 publications
0
8
0
Order By: Relevance
“…Increased oxidative damage in patients on chronic haemodialysis treatment has been considered to contribute to their increased cardiovascular risk [47][48][49], which cannot be completely explained by traditional cardiovascular risk factors and may be ameliorated with antioxidant intervention. Despite evidence for harmful effects in the general population of high doses of some common supplements (β-carotene, vitamin E, vitamin A) [50,51], there is evidence, although limited, that chronically haemodialysed patients could benefit from the use of antioxidants to prevent cardiovascular complications [52,53].…”
Section: Discussionmentioning
confidence: 99%
“…Increased oxidative damage in patients on chronic haemodialysis treatment has been considered to contribute to their increased cardiovascular risk [47][48][49], which cannot be completely explained by traditional cardiovascular risk factors and may be ameliorated with antioxidant intervention. Despite evidence for harmful effects in the general population of high doses of some common supplements (β-carotene, vitamin E, vitamin A) [50,51], there is evidence, although limited, that chronically haemodialysed patients could benefit from the use of antioxidants to prevent cardiovascular complications [52,53].…”
Section: Discussionmentioning
confidence: 99%
“… 14 , 16 , 17 Regarding HDL dysfunction in patients with ESRD, several studies have shown that HDL alters antioxidant and antiinflammatory effects in a chronic uremic state, either by a reduction in its antioxidant enzymes or by an impairment of their activity. 15 , 18 , 19 In addition, vascular smooth muscle cell hypertrophy, proliferation, and calcification have been reported to play a pivotal role in uremic vasculopathy. 20 22 Thus, vascular calcification caused by alterations in the metabolism of calcium, phosphorous, and parathyroid hormone (PTH) has been proposed as a potential risk factor for PAOD.…”
Section: Discussionmentioning
confidence: 99%
“…In patients with CKD/ESRD, the use of PPARα agonists is still controversial, and long-term safety and efficacy remain open to research [62]. By using niacin, besides having no additional benefit in patients with satisfactory control of LDL-C concentrations, tolerability was reduced [62].…”
Section: Therapy Options In Ckd/esrd For Apolipoprotein and Pcsk9mentioning
confidence: 99%
“…In patients with CKD/ESRD, the use of PPARα agonists is still controversial, and long-term safety and efficacy remain open to research [62]. By using niacin, besides having no additional benefit in patients with satisfactory control of LDL-C concentrations, tolerability was reduced [62]. ApoA-I mimetic is a new challenge for improving the lipid profile (in animal models), but clinical trials are still needed to confirm widespread use [62].…”
Section: Therapy Options In Ckd/esrd For Apolipoprotein and Pcsk9mentioning
confidence: 99%
See 1 more Smart Citation